(untitled) (Journal of Educational Sciences, 2025)
The article addresses the relevance of tolerance in the era of globalization and the importance of a tolerant approach in the formation of critical thinking of future teachers. The authors justify that tolerance promotes objective analysis, independent conclusion, and the development of information assessment skills in the critical thinking of future teachers. In addition, a tolerant approach is being studied as an integral part of the professional ethics of future teachers in the following ways: openness, willingness to take into account different opinions and cultural characteristics of students at school, humanism, empathy, responsibility, etc. The authorsconsiderscientificpublicationspublishedin the internationaldatabasesWebofScienceandScopus,inaccordancewith the topic of the articlein4directions: 1)Respect for individuality(singularity);2)Acceptance of diversity(differences);3)Listeninganddialogue;4) The ability to acceptcriticismandreach an agreement.Atthe same time,publishedscientificworksontoleranceandcriticalthinking are grouped as follows: 1)Onscientificarticles;2)Ontextbooksandmethodologicalmanuals;3)Onnormativedocumentsandinternationaldeclarations; 4)Onpsychologicaltrainingsandexercises;5)Oncasesandpracticaltasks;6)Onvideo materials andlectures;7)Onreferenceandinteractiveresources. A survey is conducted among students specialized in“PedagogyandPsychology” and“PedagogyandMethods of PrimaryEducation” of the University named after Zh.Tashenеv, the initial and final experiment carried out inaccordancewith the levels(systemicthinking,reflexive,creative,communicative,evaluative)andcomponents of tolerance(understanding,mutual understanding,cooperation).Theanalysis of the setofeffectivemethods used is carried out inaccordancewith the stages(preparation,divisionintogroupsandinstruction,structuring of criticalthinking,reflectionandgeneralization,evaluationandfeedback) of the formation of criticalthinking. Key words: tolerance, tolerant approach, critical thinking, understanding, mutual understanding, cooperation, approach.